A novel active free piston Stirling engine: Modeling, development, and experiment. (1st August 2017) - Tavakolpour-Saleh, A.R.; Zare, SH.; Bahreman, H.
Highlights: A novel active free piston Stirling engine is modeled, fabricated, and tested. A dynamic model of the engine is presented and experimentally validated. A systematic way to find gas temperature within the hot and cold spaces is proposed. The simulated thermal efficiency of 19.4% proves the potential of the concept. Abstract: This paper focuses on mathematical modeling, development, and experimental evaluation of a novel active free piston Stirling engine (AFPSE). First, working principles of the proposed AFPSE are described and its advantages are introduced. Then, a comprehensive mathematical model of the proposed Mechatronic system is presented using kinematic, dynamic, thermodynamic, heat transfer, and electrical equations. The Schmidt's theory assumptions are used throughout the modeling scheme except for finite heat transfer and imperfect regeneration. Next, a systematic way to estimate the gas temperature in the expansion and compression spaces of the engine is presented taking into account the imperfect regeneration and finite heat transfer in the presented converter. Moreover, the engine performance, as well as the resonant frequency of the active converter, is investigated through simulation. Finally, the proposed AFPSE is developed and primarily tested. The obtained practical results clearly demonstrate the feasibility of generating power (i.e. 7.1 W) through thermal excitation of a one degree-of-freedom (1-DOF) dynamic system with its resonant frequency (i.e. 9.2 Hz). Furthermore, it is found that the experimental measurements are in an acceptable agreement with the simulation outcomes of the analytical model through which validity of the mathematical scheme is affirmed.